The role of kinetic inductance on the performance of YBCO SQUID magnetometers. (7th January 2020) - Ruffieux, S; Kalaboukhov, A; Xie, M; Chukharkin, M; Pfeiffer, C; Sepehri, S; Schneiderman, J F; Winkler, D
Abstract: Inductance is a key parameter when optimizing the performance of superconducting quantum interference device (SQUID) magnetometers made from the high temperature superconductor YBa2 Cu3 O7− x (YBCO) because lower SQUID inductance L leads to lower flux noise, but also weaker coupling to the pickup loop. In order to optimize the SQUID design, we combine inductance simulations and measurements to extract the different inductance contributions, and measure the dependence of the transfer function V Φ and flux noise S Φ 1 / 2 on L . A comparison between two samples shows that the kinetic inductance contribution varies strongly with film quality, hence making inductance measurements a crucial part of the SQUID characterization. Thanks to the improved estimation of the kinetic inductance contribution, previously found discrepancies between theoretical estimates and measured values of V Φ and S Φ 1 / 2 could to a large extent be avoided. We then use the measurements and improved theoretical estimations to optimize the SQUID geometry and reach a noise level of S B 1 / 2  = 44 fT/ Hz for the best SQUID magnetometer with a 8.6 mm × 9.2 mm directly coupled pickup loop. Lastly, we demonstrate a method for reliable one-time sensor calibration that is constant in a temperature range of several kelvin despite the presence of temperature dependent coupling contributions, such as the kinetic inductance. The found variability of the kinetic inductance contribution has implications not only for the design of YBCO SQUID magnetometers, but for all narrow linewidth SQUID-based devices operated close to their critical temperature.